1997
DOI: 10.1200/jco.1997.15.2.833
|View full text |Cite
|
Sign up to set email alerts
|

High-dose cytarabine dose modification reduces the incidence of neurotoxicity in patients with renal insufficiency.

Abstract: HDAC NT is strongly associated with RI. The risk of HDAC NT can be reduced by the following: (1) routinely reducing the ARA-C dose from 3 to 2 g/m2 per dose; (2) modifying the ARA-C dose based on daily Cr values; and (3) administering HDAC on a once-daily rather than twice-daily schedule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 0 publications
0
33
0
2
Order By: Relevance
“…This is likely due to concomitant comorbidities, different disease biology, and differential chemotherapy metabolism compared to younger patients. 7,19,20 For example, older patients have a higher incidence of unfavorable chromosomal abnormalities, a lower incidence of favorable ones, and are more likely to have secondary AML. 10,[21][22][23][24][25] Patients with high risk or advanced myelodysplastic syndrome (aMDS), also a condition affecting older adults, have a disease that runs an accelerated course with a similar prognosis to patients with AML.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to concomitant comorbidities, different disease biology, and differential chemotherapy metabolism compared to younger patients. 7,19,20 For example, older patients have a higher incidence of unfavorable chromosomal abnormalities, a lower incidence of favorable ones, and are more likely to have secondary AML. 10,[21][22][23][24][25] Patients with high risk or advanced myelodysplastic syndrome (aMDS), also a condition affecting older adults, have a disease that runs an accelerated course with a similar prognosis to patients with AML.…”
Section: Introductionmentioning
confidence: 99%
“…Neurotoxicity with HDAC is thought to be related to accumulation of the neurotoxic metabolite ARA-CTP in the cerebrospinal fluid in patients with renal insufficiency [22]. In their retrospective analysis, Smith et al [37] devised a dose-modification algorithm for patients with renal impairment based on serum creatinine: (a) for patients with creatinine levels of 1.5-1.9 mg/dl or an increase in creatinine during treatment of 0.5-1.2 mg/dl, the cytarabine dose was reduced from 2-3 g/m 2 per day to 1 g/m 2 per day; and (b) for patients with creatinine levels Ն2 mg/dl or a change in creatinine Ͼ1.2 mg/dl, the dose was decreased to 0.1 g/m 2 per day.…”
Section: Cytarabinementioning
confidence: 99%
“…In spite of a correlation between elevated serum bilirubin and neurotoxicity, no algorithm for cytarabine dosing in patients with hepatic dysfunction has been developed [37].…”
Section: Cytarabinementioning
confidence: 99%
“…Furthermore, it has been shown that avoidance of very high doses of the drug in patients with renal impairment and the administration of HD-ara-C on a once-daily rather than twice-daily schedule reduce the incidence of this syndrome (Smith et al, 1997).…”
Section: Acute Encephalopathymentioning
confidence: 99%